A simple cubic sum

Algebra Level 3

Let function f ( x ) = 1 3 x 3 1 2 x 2 + 3 x 5 12 f(x)=\dfrac{1}{3}x^{3} - \dfrac{1}{2}x^{2} + 3x - \dfrac{5}{12} . What is the value of i = 1 2017 f ( i 2018 ) \displaystyle \sum_{i=1}^{2017} f \left(\frac{i}{2018}\right) ?


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Parth Sankhe
Dec 2, 2018

f ( x ) + f ( 1 x ) = 2 f(x)+f(1-x)=2

Ans:- 2 ( 1008 ) + f ( 1009 2018 ) 2(1008) + f(\frac {1009}{2018})

From the first equation, f ( 1 2 ) = 1 f(\frac {1}{2})=1

Thus, the answer is 2016 + 1 = 2017 2016+1=2017

k = 1 2017 f ( k 2018 ) = k = 1 2017 ( 1 3 ( k 2018 ) 3 1 2 ( k 2018 ) 2 + 3 ( k 2018 ) 5 12 ) = 1 3 201 8 3 k = 1 2017 k 3 1 2 201 8 2 k = 1 2017 k 2 + 3 2018 k = 1 2017 k 5 12 k = 1 2017 1 = 201 7 2 201 8 2 4 3 201 8 3 2017 2018 4035 6 2 201 8 2 + 3 2017 2018 2 2018 5 2017 12 = 201 7 2 12 2018 2017 4035 12 2018 + 3 2017 2 5 2017 12 = 2017 ( 2017 4035 ) 12 2018 + 3 2017 2 5 2017 12 = 2017 12 + 18 2017 12 5 2017 12 = 12 2017 12 = 2017 \begin{aligned} \sum_{k=1}^{2017} f \left(\frac k{2018} \right) & = \sum_{k=1}^{2017} \left(\frac 13 \left(\frac k{2018} \right)^3 - \frac 12 \left(\frac k{2018} \right)^2 + 3 \left(\frac k{2018} \right) - \frac 5{12} \right) \\ & = \frac 1{3\cdot 2018^3} \sum_{k=1}^{2017} k^3 - \frac 1{2\cdot 2018^2} \sum_{k=1}^{2017} k^2 + \frac 3{2018} \sum_{k=1}^{2017} k - \frac 5{12} \sum_{k=1} ^{2017} 1 \\ & = \frac {2017^2 \cdot 2018^2}{4\cdot 3 \cdot 2018^3} - \frac {2017\cdot 2018 \cdot 4035}{6\cdot 2\cdot 2018^2} + \frac {3\cdot 2017 \cdot 2018}{2 \cdot 2018} - \frac {5\cdot 2017}{12} \\ & = \frac {2017^2}{12 \cdot 2018} - \frac {2017 \cdot 4035}{12\cdot 2018} + \frac {3\cdot 2017}2 - \frac {5\cdot 2017}{12} \\ & = \frac {2017(2017-4035)}{12 \cdot 2018} + \frac {3\cdot 2017}2 - \frac {5\cdot 2017}{12} \\ & = - \frac {2017}{12} + \frac {18\cdot 2017}{12} - \frac {5\cdot 2017}{12} \\ & = \frac {12\cdot 2017}{12} = \boxed{2017} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...